Kuwait : Financial System Stability Assessment; Update. (IMF Staff Country Reports; Country Report, 2010)
The study shows that the global financial crisis has adversely affected Kuwait's financial system, especially in the Investment Company (IC) sector. Stress tests indicate that, in contrast to the ICs, the banking system could broadly withstand significant shocks. The Central Bank of Kuwait's (CBK) well-designed framework for banks has proven effective in shielding the banking sector from the crisis. It shows that the enactment of the capital market law is an important step toward the creation of Certified Management Accountant (CMA). The study shows that a powerful regulatory regime is needed for the insurance sector.